A DNA-based Analysis of a Microbial Technique for the Prospecting of Oil and Gas Applied to a Known Oil Field, China. Issue 1 (2nd January 2017) - Zhang, Cui-Yun; He, Ze; Zhang, Sheng; Yin, Mi-Ying; Ning, Zhuo; Liu, Ya-Ci
ABSTRACT: To evaluate the application of a DNA-based analysis of a microbial technique for oil and gas prospecting, the hydrocarbon potential predicted using the methanotrophic pmoA and propanotrophic prmA genes as targets was investigated in soil above a known oil reservoir. In total, 82 soil samples were collected at 50-cm depths above the Xiliu oil reservoir for quantitative real-time polymerase chain reaction (RT-PCR) analysis. The pmoA gene content ranged from 0 to 2.7 × 10 6 copies/g dw, whereas that of prmA varied from 0 to 1.6 × 10 6 copies/g dw. Microbial anomaly distribution maps of normalized values for the prmA gene as a main indicator suggested that the area with the highest potential of prospecting was an undeveloped location, and an area with a relatively large prmA background was identified at this oil-producing site. The areas of microbial anomaly exhibited different prmA/pmoA ratios (20, 1–5, 0.0n–0.25 and 0), and this ratio may be used as an indicator for predicting the properties of oil and gas reservoirs and biogenic methane or the influence of oil-producing activities. Our results suggest that a DNA-based analysis of a microbial technique is a powerful tool for oil and gas prospecting. This study provides a new microbial technique for the prospecting of oil and gas.